Svetlana Kurbatskaya on Serial Music: Twelve Categories of "Twelve-Toneness" - Zachary Cairns (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
Published in Moscow in 1996, Svetlana Kurbatskaya’s book Serial Music: Questions of History, Theory, Aesthetics (Seriynaya muzïka: voprosï istorii, teorii, estetiki) carries the interesting distinction of being the first Russian-language monograph devoted entirely to the study of serial music. In the second chapter, Kurbatskaya defines twelve different categories of what she calls “twelve-toneness” (dvenadtsatitonovost’). Considering this source alongside the Russian Musical Encyclopedic Dictionary (Muzïkal’nïy entsiklopedicheskiy slovar’), which includes different definitions for a number of terms that Western readers would generally consider to be essentially synonymous (i.e., serial music, serial technique, dodecaphony, twelve-tone music), one can begin to accept the possibility that Russian theorists might be more restrictive in their definitions than their Western counterparts. Despite its historical importance, Kurbatskaya’s book has remained virtually unexplored in English-language scholarship (owing both to the book’s language and relative inaccessibility in the United States). The present article aims first to summarize the state of Russian writings on serialism prior to the publication of Kurbatskaya’s book, and second to provide a thorough discussion of the second chapter of the book, which introduces twelve categories of “twelve-toneness.”